2017
DOI: 10.1364/oe.25.014644
|View full text |Cite
|
Sign up to set email alerts
|

Serial number coding and decoding by laser interference direct patterning on the original product surface for anti-counterfeiting

Abstract: Here, we investigate a method to distinguish the counterfeits by patterning multiple reflective type grating directly on the surface of the original product and analyze the serial number from its rotation angles of diffracted fringes. The micro-sized gratings were fabricated on the surface of the material at high speeds by illuminating the interference fringe generated by passing a high-energy pulse laser through the Fresnel biprism. In addition, analysis of the grating's diffraction fringes was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For example, surface functions including tribological, superhydrophobicity, and bacteria-repellency have been already demonstrated by means of DLIP in previous works [6][7][8]. It was also showed that this technology can be used for decorative applications by forming structural colors on the material surface, including in steels and polymers [9][10][11].…”
Section: Introductionmentioning
confidence: 90%
“…For example, surface functions including tribological, superhydrophobicity, and bacteria-repellency have been already demonstrated by means of DLIP in previous works [6][7][8]. It was also showed that this technology can be used for decorative applications by forming structural colors on the material surface, including in steels and polymers [9][10][11].…”
Section: Introductionmentioning
confidence: 90%
“…[1][2][3][4][5] Widely used strategies include interference lithography [3,6,7] or direct laser interference patterning. Typical implementations with diffractive optical elements, [9] beam splitters, [4,10] Fresnel biprisms, [11,12] phase masks, [13,14] or mirrors [15,16] split light into a fixed number of beams at specific angles, resulting in static periodic patterns. However, the Achilles heel of interferencebased processes is the speed of designing customized patterns.…”
Section: Light Interferencementioning
confidence: 99%
“…However, the Achilles heel of interference‐based processes is the speed of designing customized patterns. Typical implementations with diffractive optical elements, beam splitters, Fresnel biprisms, phase masks, or mirrors split light into a fixed number of beams at specific angles, resulting in static periodic patterns. Although mechanically displacing a single or multiple optical elements leads to changes in light interference, properly repositioning elements impedes real‐time selection of tailored designs.…”
mentioning
confidence: 99%
“…The fast growth of the counterfeiting market for almost all commodities including banknotes, fuels, medicine, coatings, and labels has become a serious, global, longstanding problem, which causes a huge loss of global economy, human health, and scientific development. Hence, a wide variety of anti-counterfeiting techniques and materials have been developed, separately or in combination, to combat counterfeits, including radio-frequency identification, nuclear track technology, laser holograms, and luminescent printings. , Among them, luminescent printing has been not only widely used due to its simple operation, high-throughput production, and facile design but also demonstrated to have high security potentials for many different applications . However, most of the luminescent-printed tags and patterns are still cloneable, largely because they are produced via a deterministic process and so the encrypted information stored in the luminescent tags/patterns is somehow predictable, which greatly limits their applications for high-level anti-counterfeiting. …”
Section: Introductionmentioning
confidence: 99%